Analisis Pengendalian Mutu Pekerjaan Timbunan Random Batu pada Proyek Pembangunan Bendungan Way Apu - Erwin Batista; Anjas Handayani (Riviera Publishing, 2025)
Dam is a structure consisting of earth, rock, and concrete embankments built to retain and contain water. Dam embankment work is generally carried out with the longest schedule during each dry season. The Way Apu Dam Construction Project experienced flooding due to the overflow of the Way Teba river exceeding the cofferdam on July 5, 2024, which could potentially reduce the quality of random rock embankment work. This study aims to analyze the factors that influence quality control of random rock embankment work using quantitative descriptive methods through statistical analysis with SPSS software. Data was collected through questionnaires to 44 respondents involved in the project. Factors influencing quality control were determined by multiple linear regression tests using the stepwise method. The results showed that there are 4 significant variables: